Intrinsic coordination for revealing local structural changes in protein folding–unfolding. Issue 4 (8th January 2016) - Shiu, Ying-Jen; Hayashi, Michitoshi; Shih, Orion; Su, Charlene; Tsai, Min-Yeh; Yeh, Yi-Qi; Su, Chun-Jen; Huang, Yu-Shan; Lin, Sheng-Hsien; Jeng, U-Ser
Abstract : The local dislocations may be tracked relatively easily with respect to the internal rigid rod. Abstract : With a deformed object of a rigid rod inside, the local dislocations may be tracked relatively easily with respect to the internal rigid rod. We apply this concept on protein folding–unfolding to track the internal structural changes of an unfolded protein in solution. Proposed here is a protein internal coordination based on the major axis X of an ellipsoidal protein and the stable intrinsic transition dipole momentμ of the protein during unfolding. In this methodology, small-angle X-ray scattering (SAXS) is used to provide the protein global morphologies in the native and unfolded states. Furthermore, time-resolved fluorescence anisotropy (TRFA) provides the relative orientation between X andμ of Trp59 of the model protein cytochrome c . Hence observed in the protein unfolding with denaturants, acid, urea, or GuHCl, is the elongation of the native protein conformation along a reoriented protein major axis; accompanied are the different extents of relocations of the terminal α helices and loop structures of the protein in the corresponding unfolding.